Future people : a moderate consequentialist account of our obligations to future generations - Mulgan, Tim (Clarendon Press ; Oxford University Press, 2006)
What do we owe to our descendants? How do we balance their needs against our own? Tim Mulgan develops a new theory of our obligations to future generations, based on a new rule-consequentialist account of the morality of individual reproduction. He argues that the resulting theory accounts for a wide range of independently plausible intuitions - covering individual morality, intergenerational justice, and international justice. In particular, the moderate consequentialist approach is superior to its two main rivals in this area - person-affecting theories and traditional consequentialism. The former fall foul of Parfit's Non-Identity Problem, while the latter are invariably implausibly demanding. Mulgan also claims that most puzzles in contemporary value theory (such as Parfit's Repugnant Conclusion) are actually puzzles in the theory of right action, and can only be solved if we abandon strict consequentialism for a more moderate alternative.